Geometry, materials and the imagination: a tribute to Stephen T. Hyde - Schröder-Turk,GE; Evans,ME; García-Ruiz,JM; Ninham,B; de,Campo L; Larsson,A; Craig,V; Seddon,JM; Castle,T; Nylander,T; Aste,T; Carnerup,A; et al. (Interface Focus, 2026)
Abstract This article is an introduction to a special issue of the journal ‘Interface Focus’ dedicated to Professor Stephen T. Hyde on the occasion of his retirement. Professor Hyde’s scientific career has revolved around using the geometric study of structures with negative Euler index χ—bicontinuous and other negatively curved surfaces, spatial nets, tangles and knots—to understand the emergence of shape and form in chemical and biological systems, including in lipid polymorphism, biological membranes and nanostructures, and atomic networks such as metal-organic frameworks and zeolites. Professor Hyde’s publications include articles from multiple disparate fields, including e.g. the mathematical enumeration of tillings of hyperbolic spaces and the physical chemistry of lyotropic liquid crystal polymorphism. The bulk of his work, however, comprises remarkable interdisciplinary studies that bring together fundamental geometry and applied, often experimental, science in a way where the whole truly is more than the sum of its parts. This introduction does not provide a comprehensive biography of Professor Hyde. Rather, it celebrates some of his many contributions in chronological order, together with a few anecdotes and photos, and within their historical and current context. This article includes as an appendix an unpublished manuscript entitled ‘Desperately seeking life’ by Hyde & García-Ruiz in regard to ‘biomorphs’, with shapes reminiscent of biological forms but of purely inorganic origins. This article is part of the theme issue ‘Geometry, Materials and the Imagination’.